Gauging the influence of digital ecosystem on SMEs performance among university graduates / Zuriyati Ahmad ... [et al.] - Ahmad, Zuriyati; Mahmood, Rosman; Mohd Fuza, Zatul Iffah; Mohd Redzwan, Fatimah Nur; Puteh, Mazidah (2021)
Small and Medium Enterprises (SMEs) are one of the important sectors in the economic development of a country. In the context of developing countries, the contribution of the sector is more micro, not only as a catalyst for economic growth and job creation but also has an important role in ensuring fairer income distribution, eradicating poverty, shaping industry chains and creating more balanced development. The development of the sector is no exception to the need for the application of information technology. The ability of entrepreneurs to master the digital ecosystem is a very important element to ensure the continued performance of a business. However, the majority of SMEs in Malaysia face difficulties in adapting to the digital ecosystem compared to larger enterprises. This means that SMEs are unable to create a competitive advantage through the use of digital in their business management.